2007
DOI: 10.1111/j.1748-5827.2007.00364.x
|View full text |Cite
|
Sign up to set email alerts
|

Interobserver agreement in the diagnosis of canine hip dysplasia using the standard ventrodorsal hip‐extended radiographic method

Abstract: Although interobserver agreement is low, observer experience increases agreement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
41
5
8

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(62 citation statements)
references
References 11 publications
8
41
5
8
Order By: Relevance
“…12,13 First, observers determined whether they would accept the radiograph for evaluation (radiograph is assessable or not). Secondly, observers indicated whether each coxofemoral joint was dysplastic or not, and third provided a final score for each joint according to FCIregulations (A, B, C, D, or E), 15 irrespective of whether the radiograph had been deemed assessable or not.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…12,13 First, observers determined whether they would accept the radiograph for evaluation (radiograph is assessable or not). Secondly, observers indicated whether each coxofemoral joint was dysplastic or not, and third provided a final score for each joint according to FCIregulations (A, B, C, D, or E), 15 irrespective of whether the radiograph had been deemed assessable or not.…”
Section: Methodsmentioning
confidence: 99%
“…The correct CHD diagnosis is pivotal to making sound recommendations regarding breeding programs to reduce the frequency of CHD and may prove useful in the clinical management and treatment of CHD. [3][4][5][6][7][8][9]2,[10][11][12][13][14] The CHD diagnosis is characterized by low interobserver agreement for final scoring, which could be due to improper positioning of the pelvis and/or femurs, or to insufficient radiographic contrast and/or detail. The importance of radiographic quality in the diagnosis of CHD has been described.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Analyses of inter-observer agreement of the FCI system showed that assessment of the morphological characteristics of the hip joints and the final score are highly variable between observers (Verhoeven et al 2007(Verhoeven et al , 2009). …”
Section: Extended Hip Viewmentioning
confidence: 98%
“…As part of attempts to control canine HD and reduce its incidence, several radiographic screening programs have been developed worldwide (Dennis 2012). The main canine HD scoring systems using the standard ventrodorsal hip extended (VDHE) view are those of the Fédération Cynologique Internationale (FCI), the Orthopedic Foundation for Animals (OFA) and the British Veterinary Association and the Kennel Club (BVA/KC) (Genevois et al 2007;Verhoeven et al 2007;Comhaire et al 2009;Ginja et al 2009). The relationship between the acetabular and femoral head has great importance in these radiographic screening programs (Thompson et al 2007).…”
mentioning
confidence: 99%